PR career progression - bridging the gap between traditional research and industry perception - Wolf, Katharina (Emerald Group Publishing Ltd, 2006)
Purpose:Public relations research into career advancement has been frequently criticised for its focus on gender discrimination and the prevailing dominance of American academics, while widely ignoring the perception of 'industry insiders'. This paper aims to provide new insight into PR career progression.Design/methodology/approach:The paper considers alternative aspects to PR career progression, as emphasised by general management and continuous professional development literature, with a close examination of the UK's public relations industry and its practitioners' perceptions of career advancement impacting factors.Findings:The results gained were used to develop a Five-step PR Career Progression Model, which may act as a useful starting point for further research into career advancement factors and the move towards a widely accepted set of career progression benchmarks for the UK's public relations industry.Originality/value:Overall, this paper encourages both PR academics and practitioners to work closely together on future research projects into career advancement in order to maximise the potential of the industry as a whole and improve career chances for individual practitioners.